Contrast and Island Sensitivity in Clausal Ellipsis. (26th June 2014) - Griffiths, James; Lipták, Anikó
Abstract This paper offers a comprehensive and uniform theory of island repair in clausal ellipsis (sluicing and fragments). We show that the correct generalization defines the repairing and the nonrepairing types of TP ellipsis in terms of contrastivity: TP ellipsis with contrastive remnants does not repair islands, whereas TP ellipsis with noncontrastive remnants does. Contrary to the influential account of Merchant (2004), we base our explanation for the island sensitivity of contrastive fragments entirely on the notion of Parallelism. The island insensitivity of noncontrastive remnants, on the other hand, follows from the island node being deleted at PF. With this we simplify the theory of islands, and, by treating the different types of clausal ellipsis on a par, we move away from the construction‐specific study of ellipsis that has characterized syntactic theorizing for the last forty years.